2018
DOI: 10.1017/s0007114518001101
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolamine enhances intestinal functions by altering gut microbiome and mucosal anti-stress capacity in weaned rats

Abstract: Ethanolamine (Etn) contained in milk is the base constituent of phosphatidylethanolamine and is required for the proliferation of intestinal epithelial cells and bacteria, which is important for maintenance of the gut microbiome and intestinal development. The present study investigated the effect of Etn on intestinal function and microbiome using 21-d-old Sprague–Dawley rats treated with 0, 250, 500 and 1000 μmEtn in drinking water for 2 weeks immediately after weaning. Growth performance, intestinal morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…Ethanolamine supplementation at 500 and 1000 µM significantly increased Bacteroidetes and decreased Proteobacteria, Elusimicrobia, and Tenericutes. In addition, a reduction in Spirochetes was also noticed in the mice provided with 500 µM ethanolamine [109]. Overall, most pre-clinical studies in mice have noted some impact of milk polar lipids on gut microbiota composition; however, there are differences in microbiota profiles across studies.…”
Section: Modulation Of Gut Microbiotamentioning
confidence: 84%
See 1 more Smart Citation
“…Ethanolamine supplementation at 500 and 1000 µM significantly increased Bacteroidetes and decreased Proteobacteria, Elusimicrobia, and Tenericutes. In addition, a reduction in Spirochetes was also noticed in the mice provided with 500 µM ethanolamine [109]. Overall, most pre-clinical studies in mice have noted some impact of milk polar lipids on gut microbiota composition; however, there are differences in microbiota profiles across studies.…”
Section: Modulation Of Gut Microbiotamentioning
confidence: 84%
“…In another study, Li et al [84] reported that supplementation of MFGM (200 mg/kg body weight) to C57BL/6 mice for eight weeks attenuated gut dysbiosis that occurs with HFD, including increasing the Bacteroidetes/Firmicutes ratio. Recently, modulation of the gut microbiome by ethanolamine, which is the base constituent of PE, was tested by supplementing 0, 250, 500, and 1000 µM ethanolamine to the drinking water of rats [109]. Ethanolamine supplementation at 500 and 1000 µM significantly increased Bacteroidetes and decreased Proteobacteria, Elusimicrobia, and Tenericutes.…”
Section: Modulation Of Gut Microbiotamentioning
confidence: 99%
“…The ileal and cecal contents from piglets in the control (without Cu supplementation) group and the group receiving a pharmacological dose of Cu (200 mg Cu/kg feed, n = 6 per treatment) were collected for microbiota analysis, as described previously (Zhou et al, 2018;Xiong et al, 2019). Briefly, total bacterial DNA was extracted using a QIAamp DNA Stool Mini Kit (Qiagen, Hilden, Germany), and the V3-V4 hypervariable region of the microbial 16S rRNA genes were sequenced using the primers, 341F: 5 -CCTAYGGGRBGCASCAG-3 and 806R: 5 -GGACTACNNGGGTATCTAAT-3 ; Illumina adaptors; and molecular barcodes.…”
Section: S Rdna Sequencingmentioning
confidence: 99%
“…Also, succinate is metabolite that improves glycemic control through the activation of intestinal gluconeogenesis [60]. Our previous work revealed that ethanolamine can enhance intestinal function by altering gut microbiome and mucosal anti-stress capacity [34, 61]. Moreover, L-arginine was shown to play a significant role in shaping the gut microbiota.…”
Section: Resultsmentioning
confidence: 99%
“…All procedures involving animals were carried out in accordance with guidelines for animal studies issued by the Animal Care and Use Committee of the Institute of Subtropical Agriculture, Chinese Academy of Sciences [34]. Modified hen-egg white lysozyme additives were obtained from Shanghai E. K. M Biotechnology Co. Ltd., Shanghai, China.…”
Section: Methodsmentioning
confidence: 99%